Conceptual designs of a community-based herbal manufacturing laboratory and a rural-based medicinal farming system - Casauay, Jean Flor C. 1983-
The College of Pharmacy (CP), University of the Philippine (UP) Manila has been actively participating in Community Health Development Program (CHDP), which aims to adopt local communities as partners in the promotion and delivery of health care. From 2007 to 2012, Pharmacy students underwent community immersion in San Juan, Batangas under CHDP. Having been exposed to a real primary health setting, students promoted the use of herbal preparations as the most accessible and most affordable solution to most common health problems of the community. Within the duration of the student's community immersion in San Juan, Batangas, this study was conceptualized in order to expand and strengthen the initial projects of the students. The objective of the study was to develop a guiding framework for San Juan, Batangas in setting-up an Herbal Processing and Manufacturing Laboratory as a dedicated facility for handling and manufacturing herbal products. A primary health care approach, which requires people's participation for the success and sustainability of the project, was utilized in the study. The content of the guiding framework were as follows: (1) Community Needs Assessment Survey to determine the priority herbal products needed by the community: (2) Feasibility Analysis in setting up the herbal laboratory; (3) Feasibility Analysis in setting up an herbal farm as a consistent source of plant raw materials for the laboratory; and (4) Preparation of Standard Operating Procedures (SOP) for the operation and maintenance of the Herbal Laboratory. As initiated by the academe sector, this study is envisioned to be implemented in other local communities or to every community-partner of the University in coordination with CHDP.
Available to the general public.
Thesis (Master of Science in Industrial Pharmacy) -- University of the Philippines Manila, December 2014.
Keywords: Herbal Processing and Manufacturing Laboratory